Exchange bias toggling in amine-ended single-molecule magnetic junctions by contact geometry - Tang, Yu-Hui; Chuang , Yu-Cheng; Huang , Bao-Huei (Frontiers in Physics, 2022)
The molecular scale magnetic proximity effect is proposed in single-molecule magnetic junctions (SMMJs) consisting of a dissociate amine-ended 1,4-benzenediamine (BDA) molecule coupled to two ferromagnetic Co electrodes. Our self-developed JunPy+LLG simulation combined with first-principles calculation is employed to investigate the role of contact geometry in the magnetotransport properties of SMMJs with the choice of top, bridge, and hollow contact sites. The strong spinterface effect gives rise to distinct angular dependence of equilibrium field-like spin torque (FLST), asymmetric magnetic hysteresis loop and tunable exchange bias. From the analytical derivation of nonequilibrium Keldysh formalism, we believe that a promising way forward is to activate the multi-reflection process via the so-called molecular spinterface that will allow us to conquer as-yet unexplored magnetotransport properties of organic-based spintronics.